Hu Ìwà Sí i bí Ènìyàn Ẹlẹ́ran-Ara a (act towards the other as one with human flesh): A Yoruba theory of social interactions - Akinmayowa Akin-Otiko (Social Sciences and Humanities Open)
Ubuntu has been generalized for Africa without paying attention to the plurality of cultures within the continent. This creates the need to put Ubuntu in dialogue with other African theories of social interactions. This study compares Ubuntu with the principle of Hu Ìwà síi bí Ènìyàn Ẹlẹ́ran-Ara (Act towards the other as one with human flesh), as it applies to relationships and justice. This theory was developed from the observed relationships between Yoruba traditional healthcare providers and their patients. As a theory, it assigns duty and rights to human actors in social interactions. The principle of Hu Ìwà síi bí Ènìyàn Ẹlẹ́ran-Ara is practiced among the Yoruba, and has developed into a moral system in recent researches. It shows multiplicity in African theories of social interaction. The principle was analysed and interpreted to show how it guides behaviour towards ‘the other person’ by the very fact that ‘the other’ is a human being with flesh. Contexts were analysed to establish what ought to be done to the other person as Ènìyàn eléran ara (a Human being with flesh and blood). There is a need to engage other African principles of social interaction to highlight overlaps and possible complementarities with Ubuntu.